Lookup Table Based Intelligent Charging and Balancing Algorithm for Li-ion Battery Packs - Velho, Ricardo L. (2020)
In this article, an energy storage system (ESS) and its entire monitoring system are implemented. A new charging algorithm is developed based on the parameters of the battery pack in real time, extending the battery lifespan, improving the capacity usage and performance of the ESS. The proposed algorithm analyses, in real time, the difference between the desired voltage and the mean voltage of the cells, the temperature of the pack, and the difference of voltage between cells. Based on the obtained information, by trilinear interpolation, the algorithm calculates the charging current. The proposed charging algorithm also combines a balancing algorithm. This represents an innovation compared to the existing methods in the literature. The experimental results demonstrate that the proposed algorithm can successfully charge Li-ion battery packs with different capacities and life cycles, providing a better charging time and a much lower temperature increase.